Kedudukan Ikatan Notaris Indonesia sebagai Organisasi Profesi untuk Profesi Notaris di Indonesia - Faisal Makna, Muhammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research method uses a type of normative juridical research, namely research that refers to legal norms or principles by studying and researching problems using various literature in the form of library materials or secondary data. As explained above, this research is normative legal research. Research is a tool used by humans. Based on the type of data used, it is general and specific in nature and then a conclusion can be drawn. First research result: that the Notary professional organization does not have to be single because in the provisions of Article 82 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notaries states "Notaries gather in one Notary organization". It is not interpreted as having to be single. Because the phrase "one" in the provisions of Article 82 paragraph (1) of Law Number 2 of 2014 concerning the Position of Notary Public can be interpreted as one organization whose number is neither singular nor plural. Second: Supervision of a single organization in organizational management is not optimal. Because there is a monopoly and there is also the aspirations of members which are often not conveyed or channeled. Because there is a dominant group in a single organization, a single organization does not have a healthy impact on the continuity of the life of the Notary profession.